Understanding Multicultural-Based Islamic Education - Hamid A.Ghani, Sulhan (STAI MA'ARIF MAGETAN, INDONESIA, 2021)
In a pluralistic society there are various groups of people who have different backgrounds; culture, customs, interests, language, arts, beliefs and religion, which usually face challenges of disharmony in common life and have great potential for conflict between groups; Race, Ethnicity and Religion. Conflicts with religious nuances often collaborate strongly with non-religious factors. Islam as the religion of the majority of the population in the Republic of Indonesia plays a very important role in creating an atmosphere of life full of harmony and mutual respect. In realizing this, it is necessary, among others, to carry out Islamic Religious Education with a multicultural perspective. Therefore, this study seeks to